2020
DOI: 10.1057/s41287-020-00306-8
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Private and Public Governance: The Case of Sustainability Standards for Palm Oil

Abstract: By providing insights into the interaction between private-driven and public-driven governance initiatives in the context of the “Roundtable of Sustainable Palm Oil” (RSPO) and the “Indonesian Sustainable Palm Oil” (ISPO), this article sheds new light the interaction between private and public governance. It investigates how the relationship between the RSPO and the ISPO evolves over time and who and what drives this evolution. While the interaction between these standard schemes has initially largely been cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 38 publications
(73 reference statements)
2
10
0
1
Order By: Relevance
“…It means that producers undergo multiple certification processes and make different labeling to separate logos or sustainable brands. This result is aligned with Brandi (2020), who argues that many standards in the palm oil industry create multiple costs of compliance for participants to comply with the same standards for different target markets. Second, there are no recognition and harmonization actions between SS schemes.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…It means that producers undergo multiple certification processes and make different labeling to separate logos or sustainable brands. This result is aligned with Brandi (2020), who argues that many standards in the palm oil industry create multiple costs of compliance for participants to comply with the same standards for different target markets. Second, there are no recognition and harmonization actions between SS schemes.…”
Section: Discussionsupporting
confidence: 74%
“…It can also be observed that public standards have taken advantage of benchmarking cooperation strategies. For example, in 2021, the ISPO launched a new strengthened standard for its adopters to have better possibilities of accessing international markets (Brandi, 2020; GAPKI, 2021; Kehati Foundation, 2021). Similarly, the MSPO's Secretariat informed that the MSPO–ISCC study results would be used to strengthen MSPO Principles and Criteria, including a system to harmonize the requirements under the ISCC scheme shortly (MSPO Secretariat, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are two palm oil industry certifications implemented in Indonesia, Indonesia Sustainable Palm Oil (ISPO) and Roundtable Sustainable Palm Oil (RSPO). ISPO is developed by Indonesia and recognized in the domestic market, while RSPO is initiated by Europe and is more internationally accepted [32]. As shown in table 2, ISPO is mandatory for palm oil plantations, mills, and integrated plantation mills.…”
Section: Quality Conformance Of Biodiesel and Sustainabilitymentioning
confidence: 99%